ANALISIS AKUISISI BANK AGRONIAGA OLEH BANK BRI - , Agung Sulistijo, Ahmad Djamli, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Inorganic growth is taken when internal growth is less possible, less speedy or there is another value that is to be reached. Inorganic growth can be done by way of merger or acquisition. Bank BRI, in addition to internal growth seeked in one of the strategies, they will also have inorganic growth. Acquisition of Bank Agroniaga or often called Agro bank became the choice of strategy as it is considered to provide many benefits to the Bank BRI. However, besides the value of the potential benefits, teh acquisition also will bring a lot of problems. In this study the issues to be examined are the benefits that can be obtained by Bank BRI of the target company, what is the value of teh company target if they use multiple methods of assessment and what strategies will be taken post-acquisition. In this study the data used are primary data and secondary data. Primary data was obtained from interviews with the director of teh Bank of Agriculture and related parties to Agro Bank acquisition. The secondary data was obtained from the data of publication, study reports, results of the consultans and others. By using SWOT analysis, data obtained are grouped in the table classified as strengths and opportunities owned by Bank Agronoaga, in addition to two other factors. Streghts and opportunities are the main attraction for the companies concerned and the benefits that would be obtained by Bank BRI as a buyer company. By considering the results of the external analysis and industry and adapt them to the vision and mission, SWOT analysis produces an inventory of options strategies thet can be taken post-acquisition. As for determining the value of the target company, this study used methods of assessment with a spreadsheet. To complement the assessment of teh target company, this study also included assessment using sensitivity analysis of enterprise value.